An evidence-based review of Morinda citrifolia L. (Rubiaceae) fruits on animal models, human studies, and case reports - Asman Sadino; Jutti Levita; Nyi Mekar Saptarini; Adryan Fristiohady (GarVal Editorial Ltda., 2024)
Context: Morinda citrifolia L. (Rubiaceae), commonly known as noni, is widely used as a complementary and alternative therapy in many countries due to its numerous beneficial effects on health. Aims: To thoroughly analyze the efficacy and safety of M. citrifolia fruit across all reported areas. Methods: The articles were explored on the PubMed and Cochrane Library databases using a combination of keywords: Morinda citrifolia AND human studies; Morinda citrifolia AND pharmacological activities using PRISMA guidelines. Results: Studies in animal models revealed its activity as anti-dyslipidemia, anti-lipogenesis, anti‑fungal, hepatoprotective, hypotensive, immunostimulatory, anti-alopecia, photoprotective, antitumor, antiviral, anticancer, antidopaminergic, and antimicrobial. Based on the clinical and efficacy evidence, it is apparent that M. citrifolia is a potentially valuable medicinal plant whose status should be upgraded from laboratory bench to bedside. The safety of M. citrifolia has been confirmed and proven by no occurrence of AEs or only mild gastrointestinal discomforts. However, five cases of male and female patients aged from 14 to 63 years old reported different symptoms, such as fatigue, headache, vomiting, pigmentation, or acute hepatitis, after a high-dose daily use of this supplement. Conclusions: Taking everything into consideration, M. citrifolia, despite its mild adverse events, has a beneficial efficacy and safety as an antioxidant; nevertheless, caution and therapy drug monitoring is required if this plant is to be taken in a long-term period.